EKSPLORASI WASTRA BATIK SEBAGAI MEDIA KOMPLEMEN PADA PRODUK HOME DÉCOR BERBAHAN BONGGOL JAGUNG: EXPLORATION OF BATIK WASTRA AS A COMPLEMENTARY MEDIUM IN HOME DÉCOR PRODUCTS MADE FROM CORNCOBS - Cama Juli Rianingrum; Ariesa Pandanwangi; Resky Annisa Damayanti; Ariani; MT. Ardynata (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
This research discusses development problems in the creative industry sector related to the collaboration of two different materials, namely corncob material and cloth material with batik motifs. Indonesia is rich in culture with a variety of traditional wastra or cloth, including batik cloth, woven cloth, songket cloth, and so on. Traditional batik motifs as a characteristic of Indonesian literature are very diverse and have been recognized for their beauty. A mix method was used, namely a qualitative descriptive method and an exploration of the collaboration of two different materials, namely cloth material and corncob material to become home decor products. It is hoped that with the collaborative development of this material into a more modern design work it will be able to give a new feel to a room. The aim of this research is to combine a traditional work, namely batik wastra, into a modern home décor product so that the resulting work is novel in keeping up with the times and market developments, but on the other hand, the nuances of Indonesian tradition are not lost.